Rosemary & Thyme. Series three [videorecording (DVD)] - Spence, Greg (Television producer); Kendal, Felicity; Ferris, Pam; Gunning, Chris (Distributed by Acorn Media, 2006)
Stunning locations at home and abroad provide the backdrop for this hit British mystery series. From their former careers as a university plant biologist and a police officer, Rosemary Boxer and Laura Thyme bring unique investigative talents to their horticultural and human mysteries. Their unobtrusive presence in the garden gives them unique access to secrets other detectives might miss--and that murderers would rather not reveal.